PROSTHODONTIC MANAGEMENT OF COMPROMISED RIDGES AND SITUATIONS - D., Krishna Prasad; Mehra, Divya; D., Anupama Prasad (Journal of Health and Allied Sciences NU, 2014)
Prosthodontic rehabilitation of a patient with compromised edentulous ridges in a conventional manner is a difficult task. Modifications in the treatment procedures should be considered to fulfil the patient's functional and esthetic desires. This article reviews the various compromised situations commonly encountered in a routine clinical practice and the possible management of each of them.
Keywords: Compromised ridges; abused tissues; impression techniques